Evaluation of pharmaceutical production expansion plan via batch process simulation - Tan, Jully; Foo, Dominic Chwan Yee, Assoc. Prof.; Sivakumar, Kumaresan; Ramlan, Abdul Aziz (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s homepage at http://www.myiem.org.my/